Utilização das técnicas processuais diferenciadas do mandado de segurança no procedimento comum tributário, sob a perspectiva do princípio da adequação jurisdicional - Bonomo Júnior, Aylton (2017)
This work approaches the use of differentiated procedural techniques of Writs of Mandamus within common tax procedures from the standpoint of the principle of juridical adequacy. In order to achieve a better understanding of this theme, it was opted to apportion it into four chapters. In Chapter 1, the methodological phases of the procedure are characterized highlighting its last phase (assessment-formalism), whilst concentrating greater attention on the constitutionality of the procedure and its constitutional goal: to provide effective, fair and timely judicial protection. In Chapter 2, the Writ of Mandamus, as an instrument for control of public authorities is exposed by reporting how its implementation took place in Europe and a history of how this judicial control emerged in Brazil. Chapter 3 was assigned to the study of general aspects of the Writ, specially its profile, its constitutional concept and its juridical essence of fundamental guaranty. Finally, in Chapter four, the principle of juridical adequacy (or procedural appropriateness) is analyzed under the lights of adequate judicial authority, granting the judge, in the specific case, the authority to adapt the procedure to the needs of the substantive law. Still in this chapter, comments are made on the novelty stated in art. 327, § 2º paragraph of the Civil Code, which, besides allowing for the objective accumulation of requests arising of diverse procedures, it also ensures the use of differentiated techniques in special procedures to which one or more requests are submitted. As a conclusion, the use of differentiated procedural techniques for Writs in common tax law is postulated when cumulative requests could be issued autonomously by court ruling. For this purpose, the aforementioned differentiated procedural techniques for Writs, which are compatible with common procedures, are presented herein.